2019
DOI: 10.7498/aps.68.20182052
|View full text |Cite
|
Sign up to set email alerts
|

Laser propagation transmission properties characteristics between airborne communication terminal and unmanned aerial vehicle target in complex atmospheric background

Abstract: Clouds, aerosols and atmospheric molecules are major components of the atmosphere. In the fields of atmospheric physics such as target detection, wireless optical communication and remote sensing, these atmospheric components have a strong attenuation effect on laser transmission. Based on the successive scattering method for solving the radiative transfer equation, the laser transmission model between airborne wireless optical communication terminal and ground-to-air unmanned aerial vehicle (UAV) target in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In another study [21], they found the global mean cloud radiative effects are −41.3 and −50.2 W m −2 . In 2019, M Wang et al [22] established the transmission model between the aircraft communication terminal and the UAV (Unmanned Aerial Vehicle) when the laser passed through the cirrus clouds, and analyzed the relative positions of the aircraft, UAV, and cirrus clouds, and the influence of different cirrus cloud physical properties on the laser transmission signal. However, this model only considers single-layer clouds and does not take into account the vertical structure of the clouds.…”
Section: Introductionmentioning
confidence: 99%
“…In another study [21], they found the global mean cloud radiative effects are −41.3 and −50.2 W m −2 . In 2019, M Wang et al [22] established the transmission model between the aircraft communication terminal and the UAV (Unmanned Aerial Vehicle) when the laser passed through the cirrus clouds, and analyzed the relative positions of the aircraft, UAV, and cirrus clouds, and the influence of different cirrus cloud physical properties on the laser transmission signal. However, this model only considers single-layer clouds and does not take into account the vertical structure of the clouds.…”
Section: Introductionmentioning
confidence: 99%